Kakhovska Arena's Vegetation and its Changes for 75 years (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
Peculiarities of Kachovska arena's plant cover are characterized. Floristic and coenotic diversity of areas, which were not transformed, is noted. Changes of vegetation for 75 years are analyzed. Degradation of vegetation is reviewed. Decreasing of firm- and loose-bunch grasses participation and also domination of ruderal species domination in many sand steppe communities are identified. Structure simplification of all types vegetation is found. Reduction of habitat areas is revealed both for endemic species and species of narrow ecological niche. In order to prevent further degradation of arena's plant cover it is offered to establish a reserve of 200 ha area and to include it in regional econet as a restoration area.
Keywords: arena, flora, vegetation.